PANDANGAN MAHASISWA PROGRAM STUDI ILMU ‎HUKUM TAHUN 2021 UNIVERSITAS ISLAM INDRAGIRI ‎TERHADAP HUKUM WARIS ISLAM DI INDONESIA: (Studi Komparatif Hukum Waris Islam dengan Hukum Waris Perdata dan Hukum Waris Adat) - Veronika Roselino; Herdiansyah; Bakri; M. Alfarizi (Indra Institute Research & Publication, 2023)
In this journal, the author conducts research on how the views of students of the 2021 law study program, Law Faculty, at Islamic University of Indragiri regarding inheritance law in Indonesia, as it is known that students at UNISI embrace Islam and of course also have studied and understood everything and the law regarding inheritance, whether it is Islamic inheritance law, inheritance law according to civil law or customary law itself, because basically it is not just one law that this student is studying but there are several other laws that are also being studied. In addition to religion, these students also come from diverse ethnic and cultural backgrounds, making it possible to be influenced by the perspective of these students to analyze the dynamics of inheritance law in Indonesia. In writing this journal, the author uses field research methods that use a sociological normative juridical approach, where this research is a qualitative research with data and information collection techniques using observation and interview methods. In this journal the authors found the results of this study, namely (1) that in the view of students and female students of the UNISI Law Faculty in 2021 regarding the dynamics of inheritance law in Indonesia, some of these students thought that even though there were dynamics of inheritance law in Indonesia, they believed that inheritance law based on Islamic law is the fairest law of the two other laws, namely civil law and customary law, (2) as other students have the opinion that every person who is domiciled or an Indonesian citizen has the right to choose which inheritance law they want to use in resolve disputes or problems in the inheritance law in accordance with the wishes and agreement of the heirs of the disputing families, but the best is to use Islamic inheritance law because Islam highly upholds justice especially those who are Muslim should use legal Islamic inheritance in determining the inheritance problem itself, (3) and some other students and female students assume that the dynamics of inheritance law in Indonesia is an impossibility, in essence, if there is a word of deliberation and consensus, then the issue of inheritance can be carried out properly.